2018
DOI: 10.1088/1361-651x/aa9bab
|View full text |Cite
|
Sign up to set email alerts
|

Advanced approach to the local structure reconstruction and theory validation on the example of the W L3-edge extended x-ray absorption fine structure of tungsten

Abstract: Abstract. Atomistic simulations of the experimental W L 3 -edge extended X-ray absorption fine structure (EXAFS) of bcc tungsten at T = 300 K were performed using classical molecular dynamics (MD) and reverse Monte Carlo (RMC) methods. The MD-EXAFS method based on the results of MD simulations allowed us to access the structural information, encoded in EXAFS, beyond the first coordination shell and to validate the accuracy of two interaction potential models -the embedded atom model potential and the second ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 78 publications
4
9
0
Order By: Relevance
“…At the same time, the distribution of the nearest neighbors Ba-O distances for all temperatures is noticeably wider than that for Ba-Ti as second nearest neighbor, despite that a spread of the Ba-Ti distances for equilibrium positions (1×3.370 Å, 3×3.430 Å, 3×3.501 Å and 1×3.583 Å at 40 K) is comparable to that for Ba-O (3×2.786 Å, 6×2.828 Å and 3×2.886 Å at 40 K). Usually it is expected that RDF becomes wider for further coordination shells as a correlation diminishes with increasing of the distance Jonane et al (2018). So, it is a very clear indicator that we have observed a pronounced Ba-Ti correlation in the second coordination shell of Ba.…”
Section: Resultssupporting
confidence: 54%
“…At the same time, the distribution of the nearest neighbors Ba-O distances for all temperatures is noticeably wider than that for Ba-Ti as second nearest neighbor, despite that a spread of the Ba-Ti distances for equilibrium positions (1×3.370 Å, 3×3.430 Å, 3×3.501 Å and 1×3.583 Å at 40 K) is comparable to that for Ba-O (3×2.786 Å, 6×2.828 Å and 3×2.886 Å at 40 K). Usually it is expected that RDF becomes wider for further coordination shells as a correlation diminishes with increasing of the distance Jonane et al (2018). So, it is a very clear indicator that we have observed a pronounced Ba-Ti correlation in the second coordination shell of Ba.…”
Section: Resultssupporting
confidence: 54%
“…Knowing the atomic trajectories in MD simulations, we calculate the corresponding RDFs, as well as the corresponding time-and ensemble-averaged EXAFS (MD-EXAFS). As we have demonstrated before [46,[51][52][53], MD allows one to generate EXAFS spectra in a qualitative agreement with experimental data. A very accurate agreement between MD-EXAFS and experimental EXAFS is not required here, since MD-EXAFS data are used solely for the purpose of establishing the relation between EXAFS and RDF features, and not for direct matching with ex-…”
supporting
confidence: 76%
“…4 (lower panel)). The obtained mean square displacements (MSD) σ 2 W are in agreement with previously reported experimental and theoretical results (Jonane et al (2018a)).…”
Section: Examples Of Md/rmc-exafs Applicationssupporting
confidence: 91%
“…MFP. Examples for bulk and nanocrystalline nickel oxide(Anspoks et al (2012)) and body-centred-cubic (bcc) tungsten(Jonane et al (2018a)) are shown inFig. 1.…”
mentioning
confidence: 99%